The school climate, faculty trust, and collective efficacy in a Chinese Filipino school - Sim, Luzviminda S. (Animo Repository, 2019)
According to the National School Climate Center (NSCC, 2017), school climate is the “quality and character of school life.” Based on current research, two of the hypothetical catalysts for the school climate are trust (Tschannen-Moran, 2014a; Zeinabadi, 2014) and collective efficacy (Johnson, 2012; Stokes, 2016; Ware & Kitsantas, 2007). Therefore, this study of Chinese Filipino school climate underscored the importance of its relationship and significant influence on faculty trust and collective efficacy. A mixed method research design was used to collect and analyze data. The study sample consisted of 222 teachers, staff, and administrators employed in a Chinese Filipino school in Manila. School Climate Index (SCI), Omnibus Trust Scale (OTS), and Collective Efficacy (CE) Scale were used to gather quantitative data. While 20 purposively selected teachers participated in the focus group interviews. Correlational results corroborated strong to moderate positive relationship between school climate, faculty trust and collective efficacy. As school climate becomes positive and healthy, the higher level of faculty trust and collective efficacy. Regression models confirmed that faculty trust and collective efficacy constructs ensue different Chinese Filipino school climate predictors. Noteworthy was the finding that collegial leadership did not predict trust in colleagues, trust in clients, and collective efficacy. Consequently, interview results supported the statistical findings. This study provided school leaders with framework to gain insights into Chinese Filipino school climate in building trust and efficacy. Recommendations for future research are proposed for school leaders to provide logical expansion of the study.